Meningococcal disease. Meningococcal conjugate polysaccharide vaccines and new generation vaccines. Report 3 - M. V. Abramtseva; A. P. Tarasov; T. I. Nemirovskaya (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Despite the progress in fighting against infectious diseases of bacterial origin, the incidence of generalized forms of meningococcal infection (GFMI) remains a topical public health problem not only in countries with historical high incidence, but also in countries considered to be relatively «secured» in regard to the mentioned infection. In the 60s of the last century the production of high-polymer forms of meningococcal polysaccharides was started. These high molecular weight polysaccharides were used for the development of vaccines. They helped to significantly reduce the incidence of GFMI in certain countries, including the countries of the so-called African «meningitis belt». Unfortunately, polysaccharide vaccines have well-known deficiencies, prompting the researchers to develop advanced conjugate vaccines. Current new generation of vaccines are based on conjugates of polysaccharides of different serogroups with carrier proteins such as tetanus toxoid, a modified diphtheria toxin (CRM197) or outer membrane proteins. Mono- and multivalent conjugate vaccines were developed and tested. Conjugate vaccines have several advantages compared to the polysaccharide vaccines. They stimulate the formation of immunological memory, and therefore are able to provide consistent protection against meningococcal disease in children of an early age group. In particular, monovalent conjugate vaccine against serogroup C meningococcal disease were proven to be very effective. This vaccine was successfully used in the UK. There are also tetravalent conjugate vaccines Menactra and Menveo. These preparations consist of serotype A, C, W135 and Y meningococcal polysaccharide conjugates. These polysaccharides stimulated the production of bactericidal antibodies in 90% of immunized individuals. Certain success was also achieved in developing genetically engineered vaccines and the vaccines based in meningococcal outer membrane vesicles (OMV-vaccines). OMV-vaccines showed to be effective in the fight against epidemics of meningitis caused by serogroup B meningococcus. Polysaccharide vaccines against serogroup B meningococcus in different designs proved to be ineffective because of their low immunogenicity. There are certain difficulties in developing an ultimate vaccine that protects against GFMI, due to the fact that there is a variety of antigenic types of serogroup B meningococcus. So far the scientists only have managed to develop a strain-specific vaccine suitable for fighting GFMI outbreaks, caused by the specific strain of serogroup B meningococcus. The opportunities to enhance the efficacy of vaccines against serogroup B meningococcus are still being discussed.